2022
DOI: 10.1029/2021jg006698
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and Duration of Nitrogen Addition Jointly Alter Soil Nutrient Availability in a Temperate Grassland

Abstract: Increasing N input can alter soil nutrient availability and influence plant growth. Previous studies focused on N addition effects on N and P availability, while less on other mineral nutrients. Besides, how N addition duration affects nutrient availability has remained unclear. Based on a simulative N deposition experiment in a typical steppe with four N addition levels (0, 2, 10, and 50 g m−2 yr−1) under three N addition duration (2, 5, and 10 years), we determined contents of 10 mineral nutrients in surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…However, excessive N inputs can increase the leaching of base cations from the soil. When N is added in excess, it can cause imbalances in nutrient availability and uptake by plants (Niu et al 2022). Such imbalances can result in decreased uptake of base cations, leading to their leaching out of the soil profile with percolating water (Sverdrup and Rosen 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive N inputs can increase the leaching of base cations from the soil. When N is added in excess, it can cause imbalances in nutrient availability and uptake by plants (Niu et al 2022). Such imbalances can result in decreased uptake of base cations, leading to their leaching out of the soil profile with percolating water (Sverdrup and Rosen 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of edaphic factors, such as nutrient availability, spatial factors, such as underlying fertility and history of deposition interact with future loading. Ecosystem responses have also been shown to vary with the intensity and duration of the treatment (Niu et al, 2022). This means that it is often difficult to (explicitly) generate hypotheses that reflect multiple known individual processes and their (unknown) interactive effects.…”
Section: Hypothesis Generation and Experimental Designmentioning
confidence: 99%
“…As a result, we observed significant interaction effects of N and water addition in most soil layers (Table S2). Second, soil N availability for plants and microbial communities would be altered with increasing intensity and duration of N addition (Elser et al 2010;Niu et al 2022a). In the long run, plant growth processes and plant residue inputs into the soil varied significantly under low-and high-N addition rates (Bai et al 2010), which may further affect soil C and nutrient cycling.…”
Section: Effect Of N Addition On Topsoil C:n:p:s Stoichiometry Depend...mentioning
confidence: 99%
“…An increasing number of research demonstrated that soil total C, N, P, and S contents declined as soil depth increased, but fewer studies have examined changes in their ratios along the soil profile (Manzoni et al 2010;Khan et al 2016;Chen et al 2016;Niu et al 2022a). Based on the decreasing trends of soil C:N and C:P ratios with soil depth and the increasing trends of soil N:P, N:S, and P:S ratios regardless of N and water addition, it may be inferred that C and N are the key factors limiting the microbial activity in deep soil.…”
Section: Effect Of N and Water Addition On Soil C: N: P: S Stoichiome...mentioning
confidence: 99%